1992
DOI: 10.1136/bjo.76.5.275
|View full text |Cite
|
Sign up to set email alerts
|

Retinal blood flow alterations associated with scleral buckling and encircling procedures.

Abstract: The bidirectional laser Doppler technique and monochromatic photography were used to measure the absolute blood flow rate in the majortemporal retinal arteries in seven patients foliowing unilateral scleral buckling and encircling procedures, and in two patients before and after removal of scleral buckling elements. In the seven patients who had undergone uncomplicated scleral buckling procedures the arterial flow rates were on average 50% lower (p=0-01) in the surgicaily treated eyes than in the contralateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
2
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 8 publications
2
51
2
2
Order By: Relevance
“…Several pre-and postoperative factors such as the long duration of macular detachment, alterations in retinochoroidal circulation, and ciliary edema have been reported to be associated with poor visual outcomes of the scleral buckling surgery. [26][27][28][29][30] Our results revealed that the mean comaand spherical-like aberrations at 3 postoperative months were 0.385 ± 0.267 and 0.271 ± 0.156, respectively. Pesudovs et al revealed that coma-and spherical-like aberrations for 6-mm pupils in patients with various types of spherical intraocular lenses (IOLs) were 0.37-0.51 and 0.36-0.60, respectively.…”
Section: Discussionmentioning
confidence: 72%
“…Several pre-and postoperative factors such as the long duration of macular detachment, alterations in retinochoroidal circulation, and ciliary edema have been reported to be associated with poor visual outcomes of the scleral buckling surgery. [26][27][28][29][30] Our results revealed that the mean comaand spherical-like aberrations at 3 postoperative months were 0.385 ± 0.267 and 0.271 ± 0.156, respectively. Pesudovs et al revealed that coma-and spherical-like aberrations for 6-mm pupils in patients with various types of spherical intraocular lenses (IOLs) were 0.37-0.51 and 0.36-0.60, respectively.…”
Section: Discussionmentioning
confidence: 72%
“…While a drastic change in the intraocular environment has been emphasized with vitrectomy, choroidal circulation disturbance does occur following scleral buckling 24 and a high incidence of macula edema after scleral buckling has been reported. 25 We have also experienced a case in which postscleral buckling visual acuity had dropped significantly in eyes with intact macula and good preoperative vision (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The methodology of our application of the laser Doppler technique to measurement of centerline blood speed in retinal arteries has been described in detail [34]. Modifications to the methodology have also been described [35]. Our projection micrometry technique for measurement of arterial diameters using mono chromatic photographs has also been described [36].…”
Section: Ethodsmentioning
confidence: 99%